2013
DOI: 10.1159/000353613
|View full text |Cite
|
Sign up to set email alerts
|

The Link between High-Sensitivity C-Reactive Protein and Orbitofrontal Cortex in Euthymic Bipolar Disorder

Abstract: Objective: C-reactive protein (CRP), a marker of underlying low-grade inflammation, has been associated with the pathophysiology of bipolar disorder. Additionally, bipolar disorder may be accompanied by functional or structural cerebral alterations. We attempted to discover whether serum high-sensitivity CRP (hs-CRP) levels are linked to the structural volume change of a specific brain region along with cognitive performance. Methods: We recruited 17 physically healthy patients with bipolar I disorder (DSM-IV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
4
17
1
Order By: Relevance
“…As for bipolar disorder, we found a nominal effect of a 1.21-fold increase in risk for bipolar disorder with a 10-s% increase in CRP level. Though this nominal predisposing effect needs to be confirmed, our finding corroborates epidemiological observations suggesting that elevated CRP is associated with the disease and supports a potential causal influence of general inflammation in bipolar disorder [ 86 ]. We note that, though it may be biologically sensible, this result failed to pass multiple testing correction.…”
Section: Discussionsupporting
confidence: 88%
“…As for bipolar disorder, we found a nominal effect of a 1.21-fold increase in risk for bipolar disorder with a 10-s% increase in CRP level. Though this nominal predisposing effect needs to be confirmed, our finding corroborates epidemiological observations suggesting that elevated CRP is associated with the disease and supports a potential causal influence of general inflammation in bipolar disorder [ 86 ]. We note that, though it may be biologically sensible, this result failed to pass multiple testing correction.…”
Section: Discussionsupporting
confidence: 88%
“…Preliminary evidence of persistent CNS‐driven inflammation is also provided by a [ 11 C]‐(R)‐PK11195 positron emission tomography (PET) study that identified increased microglial activation in the right hippocampus of euthymic individuals with BD . Extending from these observations, peripheral and central markers of inflammation have been associated with cognitive dysfunction in euthymic and symptomatic individuals with BD (for reviews of cognitive deficits and underlying neurobiological models, the reader is referred to the Mood Disorders – Neurocognition special issue of Bipolar Disorders ). Taken together, the available evidence provides a rationale for testing the hypothesis that concurrently mitigating both peripheral and central inflammation may alleviate depressive and cognitive symptoms of BD.…”
Section: Introductionmentioning
confidence: 98%
“…Direct evidence of neuroinflammation has been scarcer, but has supported the hypothesis of inflammatory dysregulation [3][4][5]. In addition, inflammatory mediators have been consistently associated with neurostructural abnormalities in individuals with BD [6][7][8][9][10]. As a result, anti-inflammatory agents have been recently tested as therapies for mood disorders, including bipolar depression [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: TNFR1: Tumour necrosis factor-alpha receptor-1; NF-κB: nuclear factor-kappa B; PA: with clinically significant history of physical abuse; No PA: without clinically significant history of physical abuse. Cells 2020,9, 895…”
mentioning
confidence: 99%